Ultrasonic Assessment of Females with Carpal Tunnel Syndrome Proved by Nerve Conduction Study - Ihsan M. Ajeena; Raed H. Al-Saad; Ahmed Al-Mudhafar; Najah R. Hadi; Sawsan H. Al-Aridhy (Neural Plasticity)
Introduction. Carpal tunnel syndrome (CTS) is the most commonly diagnosed entrapment neuropathy of the upper extremity. The objective of this study was to diagnose CTS and to assess its severity using high resolution ultrasound (HRUS) depending on the results of nerve conduction study (NCS). Methods. A prospective cross-sectional study, in which HRUS was performed at 63 wrists of 35 female patients with different severity of CTS (as proved by NCS). Furthermore, 40 healthy volunteers (80 wrists) underwent the same tests as the patients and have been chosen to match the patients in gender, age, and body mass index (BMI). The cross section area (CSA) of the median nerve (MN) was obtained using HRUS at the carpal tunnel inlet by direct tracing method. Results. There was a significant difference in the CSA of the MN at the tunnel inlet in CTS patients when compared with the control group. In fact, the CSA of the control group showed a significant difference from each of patients subgroups. Furthermore, a significant difference in the CSA was seen in between these subgroups. In conclusion, the US examination of the MN seems to be a promising method in diagnosing and grading of carpal tunnel syndrome.